2022
DOI: 10.3389/fmed.2021.775587
|View full text |Cite
|
Sign up to set email alerts
|

MPMR: Multi-Scale Feature and Probability Map for Melanoma Recognition

Abstract: Malignant melanoma (MM) recognition in whole-slide images (WSIs) is challenging due to the huge image size of billions of pixels and complex visual characteristics. We propose a novel automatic melanoma recognition method based on the multi-scale features and probability map, named MPMR. First, we introduce the idea of breaking up the WSI into patches to overcome the difficult-to-calculate problem of WSIs with huge sizes. Second, to obtain and visualize the recognition result of MM tissues in WSIs, a probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, multiple studies show applications in the differentiation between melanoma, nevi, and normal skin [ 34 , 35 ]; and differentiation between melanoma and nonmelanoma skin cancers [ 36 , 37 , 38 ]. Several studies showed deep-learning applications for the segmentation of whole tumor regions [ 39 , 40 , 41 , 42 ] or individual diagnostic markers such as mitotic cells [ 43 , 44 ], melanocytes [ 45 , 46 ], and melanocytic nests [ 47 ]. Several of these models were compared against the diagnostic accuracy of trained histopathologists, showing improved performance [ 25 , 27 , 29 , 31 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, multiple studies show applications in the differentiation between melanoma, nevi, and normal skin [ 34 , 35 ]; and differentiation between melanoma and nonmelanoma skin cancers [ 36 , 37 , 38 ]. Several studies showed deep-learning applications for the segmentation of whole tumor regions [ 39 , 40 , 41 , 42 ] or individual diagnostic markers such as mitotic cells [ 43 , 44 ], melanocytes [ 45 , 46 ], and melanocytic nests [ 47 ]. Several of these models were compared against the diagnostic accuracy of trained histopathologists, showing improved performance [ 25 , 27 , 29 , 31 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the design of the shape encoder network, we introduce the deformable kernel to address the limitation of the rectangular receptive field of the convolution kernel. Irregular-shaped visual features are common in lesion images, for example, the irregular-shape boundary of the lesion in dermoscopic images (Celebi et al, 2019 ), the irregular-shaped cells in pathological images (Zhang D. et al, 2022 ). Rectangular convolutional kernels have limitation in extracting these features, especially in extracting low-level shape features.…”
Section: Methodsmentioning
confidence: 99%
“…We compared the proposed method with some popular general vision models, including the ResNeSt (Zhang H. et al, 2022 ), which is the latest iteration of ResNet, and ConvNeXt (Liu et al, 2022 ), which is regarded as CNN for 2020s. We also added some models designed for specific medical image recognition tasks to the comparative experiment, including DeMAL-CNN (He et al, 2022 ) for skin lesion classification in dermoscopy images, and MPMR (Zhang D. et al, 2022 ), which is a multi-scale-feature-based melanoma recognition method in pathological images.…”
Section: Methodsmentioning
confidence: 99%